2002
DOI: 10.1124/jpet.102.040600
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive-Protein-Associated Increase in Myocardial Infarct Size After Ischemia/Reperfusion

Abstract: C-Reactive protein (CRP), a marker for acute inflammation, is associated with increased risk of cardiovascular events. The mechanism underlying this association is uncertain. An acute inflammatory response was induced in rabbits by subcutaneous injection of croton oil (CO) 1 to 3 days before 30 min of regional myocardial ischemia/180 min of reperfusion. CO treatment increased plasma CRP from below the limit of detection to 2.5 Ϯ 0.5 mg/dl and was associated with an increase in infarct size expressed as percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
57
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 37 publications
3
57
0
3
Order By: Relevance
“…Systemic administration of CRP was found to increase the extent myocardial necrosis, through complement-dependent mechanisms, in experimental acute myocardial infarction (Griselli et al, 1999). The endogenous production of CRP in response to a remote inflammatory response likewise results in more extensive myocardial injury after ischemia/reperfusion (Barrett et al, 2002). CRP has been shown to activate the classical complement pathway providing a possible mechanism linking CRP to mortality due to myocardial infarction (Kaplan and Volanakis, 1974;Wolbink et al, 1996;Nijmeijer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic administration of CRP was found to increase the extent myocardial necrosis, through complement-dependent mechanisms, in experimental acute myocardial infarction (Griselli et al, 1999). The endogenous production of CRP in response to a remote inflammatory response likewise results in more extensive myocardial injury after ischemia/reperfusion (Barrett et al, 2002). CRP has been shown to activate the classical complement pathway providing a possible mechanism linking CRP to mortality due to myocardial infarction (Kaplan and Volanakis, 1974;Wolbink et al, 1996;Nijmeijer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Once thought of as only a nonspecific indicator of systemic inflammation, recent epidemiological research indicates that CRP might be directly involved in the pathogenesis of ischemic diseases through the activation the complement system (Beranek, 1997;Du Clos, 2000;Agrawal et al, 2001). Previous studies have demonstrated that plasma CRP concentration is directly related to infarct size following ischemia/reperfusion (Barrett et al, 2002;Hirschfield and Pepys, 2003).…”
mentioning
confidence: 99%
“…In Pool et al study, preoperative symptoms were associated with postoperative hospital stay [16]. For example, in acute myocardial infarction, CRP measurement is the best and most sensitive test that can obtain signs of necrosis or inflammation of myocardium [17] [18]. In coronary arteries stenosis, CRP is positive in cases with necrosis and negative in cases without necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…14 In experimental studies, increased C-reactive protein levels aggravate infarct size. 15 The importance of systemic inflammatory changes for extension of the infarcted myocardium was further confirmed in clinical studies demonstrating that the inflammatory response is predictive for the amount of salvaged myocardium. 16 Moreover, inflammatory markers such as IL-6, IL-8, or MCP-1 are elevated in AMI 17 and are predictive for recurrent plaque instability.…”
mentioning
confidence: 87%